PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KOMPUTASI SISWA KELAS VIII SMP CINTA RAKYAT 3 PEMATANGSIANTAR - Malau, Octo Laura; Sidabutar, Ropinus; Tambunan, Lois Oinike (MES: Journal of Mathematics Education and Science, 2025)
Abstract. This study aims to determine the effect of the problem-based learning model on the computational thinking skills of eighth-grade students at SMP Cinta Rakyat 3 Pematangsiantar on the subject of two-variable linear equation systems. The method used in this study was based on quasi-experimental research with a purposive sample of 30 students. The instruments used were tests and questionnaires that had been declared valid and reliable. The hypothesis test used was the t-test and the coefficient of determination. Based on the results of data analysis, it can be concluded that there is a significant effect of the use of the Problem-Based Learning model on the computational thinking skills of eighth-grade students at SMP Cinta Rakyat 3 Pematangsiantar in the 2025/2026 academic year. This positive effect is shown through the regression equation Y = 11.325 + 0.275X with a b value of 0.275. The contribution of the problem-based learning model to students' computational thinking skills is 72.9%.